Poverty and Labor Force Participation in Jambi Province: A Panel Data Analysis - Sani, Sri Rosmiati; Amri, Khairul; Fitri, Cut Dian; Bakar, Jariah Abu (Badan Pengembangan Sumber Daya Manusia (BPSDM) Provinsi Jambi, 2025)
Introduction/Main Objective: Labor force participation is crucial for improving household economic conditions. Theoretically, labor force participation in the job market can be influenced by several factors, including poverty levels. Documentation from the Central Bureau of Statistics (BPS) of Jambi Province indicates that labor force participation rates vary across districts and cities in the province. This study aims to estimate the impact of poverty levels on labor force participation rates in Jambi Province. In this analysis, labor force participation is categorized into male and female labor force participation rates. Research Methodology: This study employs panel data from districts and cities during the 2018–2023 period. All data are sourced from published reports by the Central Bureau of Statistics (BPS) of Jambi Province. To estimate the relationship between variables, the study utilizes panel regression analysis with a fixed-effects approach. Findings/Results: The study demonstrates that poverty levels have a positive and significant impact on male and female labor force participation rates. The higher the poverty level, the higher the male and female labor force participation in the job market. Conversely, lower poverty levels are associated with lower labor force participation rates. Conclusion/Recommendations: Labor force participation in the job market is significantly determined by poverty levels. In other words, the challenges faced by households in meeting their basic needs drive increased participation in the job market. Therefore, it is recommended that district and city governments in Jambi Province enhance labor force participation by providing training and skills development programs, particularly for impoverished groups.